Isolation and Molecular Identification of Lactic Acid Bacteria from Robusta Coffee Fermentation and Antifungal Test against Penicillium sp. - Salsabila.JS, Nurfitrah; Jannah, Siti Nur; Nurhayati, Nurhayati (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2022)
Lactic acid bacteria (LAB) play an important role in robusta coffee fermentation by soaking coffee beans. Spontaneous fermentation of coffee beans can improve coffee quality by producing organic acids and volatile compounds. The ability of LAB to produce organic acids also has the potential as an antifungal compound. Penicillium is one of the predominant contaminants of coffee beans products in Indonesia. Coffee beans can become contaminated by Penicillium during various stages such as harvesting, processing, transport, and storage. To prevent contamination of coffee beans, new preservation methods involving biological agents, such as lactic acid bacteria, may be used instead of chemicals. The secondary metabolites produced by LAB can be utilized for bio preservation. Lactic acid bacteria in robusta coffee fermentation should be further explored and analyzed for antifungal activity against Penicillium sp., and molecularly identified to determine the spesies of lactic acid bacteria that have antifungal potential. The isolation method was carried out using multilevel dilution and spread plate on MRSA+CaCO3 media. Identification was conducted through macroscopic and microscopic observation of cells and their characteristics, as well as molecular identification. Antifungal testing was performed using the agar well diffusion method. The results of LAB isolation yielded 12 LAB isolates with characteristics of round colony shape, gram-positive, rod and round cell shape, with negative catalase. The test results showed that isolates BKR 4, BKR 11, BKR 12 exhibited antifungal activity. BKR11 isolate was identified as Leuconostoc mesenteroides.